Effect of production system on physical–chemical, antioxidant and fatty acids composition of Longissimus dorsi and Serratus ventralis muscles from Iberian pig - Tejerina, D; García-Torres, S; Cabeza de Vaca, M; Vázquez, F M; Cava, R (Food Chemistry, 2012)
The effect of three production systems of Iberian pigs namely Montanera (free-range system and feeding based on acorns and grass), Recebo (free-range system and nutrition based in combination of acorns, grass and mixed feeds) and Intensive (conﬁnement with mixed feeds) on some quality traits of Longissimus dorsi (LD) and Serratus ventralis (SV) muscles were studied. Muscles from pigs raised in the Montanera system showed signiﬁcantly higher CIE L ⁄ , a ⁄ and b ⁄ values and higher haem pigment content than those from Intensive system. Similarly, muscles from pigs raised in the Montanera system had signiﬁcantly higher contents of a and c-tocopherol and phenolic compounds contents and higher lipophilic and hydrophilic activity antioxidant than those from pigs raised in the Intensive system. Fatty acids proﬁles from Montanera pigs had signiﬁcantly higher monounsaturated (MUFA) and polyunsaturated (PUFA) fatty acids and lower saturated fatty acids (SFA) than those from pigs raised in the Intensive system. In relation to muscle effect, LD showed lower intramuscular fat (IMF), a-tocopherol, phenolic compounds, lipid oxidation and PUFA, but higher MUFA than SV.
Keywords: antioxidant; fatty acids; Iberian pigs; Montanera

Study of variability in antioxidant composition and fatty acids profile of Longissimus dorsi and Serratus ventralis muscles from Iberian pigs reared in two different Montanera seasons. - Tejerina, D; García-Torres, S; de Vaca, M Cabeza; Vázquez, F M; Cava, R (Meat science, 2012)
This investigation was designed to evaluate the effects of variations in antioxidant and fatty acids composition of acorns and grass from two Montanera (free-range system and feeding based on acorns and grass) seasons (2006/07 and 2007/08) on the antioxidant composition and fatty acids profile of m. Longissimus dorsi (LD) and m. Serratus ventralis (SV) from Iberian pigs reared under these Montanera seasons. Acorn and grass composition was affected by Montanera season and consequently, LD and SV muscles showed different contents of α-tocopherol, total phenols, hydrophilic and lipophilic antioxidant activity and fatty acid profile, according with the composition of acorns and grass ingested. Results suggest a lack of uniformity in meat quality between different seasons. This could be due to the variable nature of extensive pig production as reflected in the variability in the composition of the diet (acorns and grass).
Keywords: acorns; diet composition; Grass; Iberian pigs; meat; Montanera

Dimensiones y características nutritivas de las bellotas de los Quercus de la dehesa - Rodríguez-Estévez, V; García Martínez, A; Mata Moreno, C; Perea Muñoz, J M; Gómez Castro, A G (Arch. Zootec, 2008)
Acorns production of Quercus (Q. ilex, Q. suber, etc.) is an important feeding resource in the dehesa during autumn-winter. Acorn weight, size and shape present a lot of variability between species, species, individuals and areas. Also composition is variable and is influenced by its own maturation process and external agents (humidity, parasites, etc.). Op.osite, shell and cotyledons proportions show higher homogeneity. Shell composition has a very high level of tannins and lignin, which affects its digestibility. Kernel has a very high level of glucids (80% of DM) and lipids (5-10% of DM) with a oleic acid content up.er 60%, however protein level is very low (4-6% of DM). Many wild and domestic species eat acorns; however, in the dehesa, acorns are used to feed fattening Iberian pigs because this breed is the single one capable of peeling them and rises a high commercial value
Keywords: fatty acids; iberian pig; Montanera; Quercus ilex; Quercus suber; Sus scrofa

Dimensiones y características nutritivas de las bellotas de los Quercus de la dehesa - Rodríguez-Estévez, V.; García Martínez, A.; Mata Moreno, C.; Perea Muñoz, J. M.; Gómez Castro, A. G. (Arch. Zootec, 2008)
Acorns production of Quercus (Q. ilex, Q. suber, etc.) is an important feeding resource in the dehesa during autumn-winter. Acorn weight, size and shape present a lot of variability between species, species, individuals and areas. Also composition is variable and is influenced by its own maturation process and external agents (humidity, parasites, etc.). Op.osite, shell and cotyledons proportions show higher homogeneity. Shell composition has a very high level of tannins and lignin, which affects its digestibility. Kernel has a very high level of glucids (80% of DM) and lipids (5-10% of DM) with a oleic acid content up.er 60%, however protein level is very low (4-6% of DM). Many wild and domestic species eat acorns; however, in the dehesa, acorns are used to feed fattening Iberian pigs because this breed is the single one capable of peeling them and rises a high commercial value
Keywords: fatty acids; iberian pig; Montanera; Quercus ilex; Quercus suber; Sus scrofa

Producción de bellota en la dehesa: factores influyentes - Rodríguez-Estévez, V.; García, A.; Perea, J.; Mata, C.; Gómez, A. G. (Arch. Zootec, 2007)
This paper reviews the state-of-the- knowledge of acorn production in the South- Western Iberian dehesas. In the first part are briefly described the soil and climatic determining factors and phenology of most common trees of genus Quercus at the dehesa (Q. ilex, Q. suber and Q. faginea). In the second part, acorn production estimations are analyzed. Was established a mean acorn yield of 300 to 700 kg/ ha; with individual productions of 8-14 kg/tree for Q. ilex, 5-10 kg/tree for Q. suber and 1-11 kg/ tree for Q. faginea; with a highly variable production, both between and within years and individual trees. Finally we review the factors affecting acorn production, describing density of trees (estimated in 20-50 trees/ha), masting phenomenon (with cycles of 2-5,5 years and asynchrony between trees), individual cha- racteristics of trees (genetic potential, age, top surface, etc.), tree mass handling (with favourable effect of tilling, moderate pruning and sustainable grazing), meteorological conditions (mainly drought and meteorology during flowering) and sanitary status (Lymantria, Tortrix, Curculio, Cydia, Balaninus and Brenneria).
Keywords: Agro forestry system; evergreen oak; iberian pig; Mast-seeding; Montanera; Quercus

Producción de bellota en la dehesa: factores influyentes - Rodríguez-Estévez, V; García, A; Perea, J; Mata, C; Gómez, A G (Arch. Zootec, 2007)
This paper reviews the state-of-the- knowledge of acorn production in the South- Western Iberian dehesas. In the first part are briefly described the soil and climatic determining factors and phenology of most common trees of genus Quercus at the dehesa (Q. ilex, Q. suber and Q. faginea). In the second part, acorn production estimations are analyzed. Was established a mean acorn yield of 300 to 700 kg/ ha; with individual productions of 8-14 kg/tree for Q. ilex, 5-10 kg/tree for Q. suber and 1-11 kg/ tree for Q. faginea; with a highly variable production, both between and within years and individual trees. Finally we review the factors affecting acorn production, describing density of trees (estimated in 20-50 trees/ha), masting phenomenon (with cycles of 2-5,5 years and asynchrony between trees), individual cha- racteristics of trees (genetic potential, age, top surface, etc.), tree mass handling (with favourable effect of tilling, moderate pruning and sustainable grazing), meteorological conditions (mainly drought and meteorology during flowering) and sanitary status (Lymantria, Tortrix, Curculio, Cydia, Balaninus and Brenneria).
Keywords: Agro forestry system; evergreen oak; iberian pig; Mast-seeding; Montanera; Quercus

Sustained utilization of the Iberian pig breed. - López-Bote, C J (Meat science, 1998)
The Iberian pig is one of the scarce non-improved swine breeds which survives the modern techniques of pig production based on improved genotypes. This is attributed both to its perfect adaptation to the Mediterranean natural ecosystem and the high quality of its products. The production of meat products from Iberian pigs has very little in common with that of meat products obtained from selected pigs raised under intensive conditions, and it constitutes an example of the preparation of high quality meat products, comparable to the most exquisite food products in the world. The production of Iberian pig is deeply bound to the Mediterranean ecosystem. It is a rare example in the world swine production where the pig contributes so decisively to the preservation of the ecosystem. The aim of this review is to describe in detail the traditional feeding of the Iberian pigs in La Dehesa and to discuss some aspects of the use of alternatives to this production system. Some of the experience in the formulation of compounds feeds for Iberian pigs and in the processing of meat products could be useful in the feeding of other pig genotypes and in different meat processing strategies.
Keywords: Dehesa; high quality products (voyant); iberian pig; Meat Products; Montanera

Influencia de la suplementación proteica en las producciones del cerdo Ibérico en la Dehesa - LÓPEZ DE TORRE, GUILLERMO; BENITO HERNÁNDEZ, JOSÉ; FERRERA CLARAMONT, JOSÉ LUIS (Pastos, 1983)
The effect of adding 15 percent soybean meal to the summer cereal ration has been studied. Also the addition of 15 percent vs 5 percent soy- bean meal to a cereal mixture has been compared during the fattening period in the autumn when they were giving oak acorns under grazing conditions. Those effects were measured on weights at the end of sum- mer and fall, gains, feed effeciency and carcass characteristics. Four groups of 20 castrated pigs (10 males and 10 females) chosen at random were made. Average rate of gain was higher (460 vs 395 gr./day, p <^ 0,01) and food conversión was better (3,98 vs 4,64) for pigs receiving 15 percent soybean meal during summer. Protein contení of ration during fall while grazing on the oak fields did not affect gains. Carcass characteristics were not influenced by summer protein percent and, only some of them as carcass yield and back fat thickness were affected by fall protein percent. Sex affected all weights and gains considered. These results suggest that high protein rations during summer may result in improved productions at the end of the following acorn crop period. PASTOS
Keywords: aumento de peso; cerdo Ibérico (voyant); Montanera; suplementación de proteína